Factors Affecting Student Satisfaction and Loyalty in Selected Universities in Phnom Penh: A Structured Literature Review - Chanbolin Heng; Dr. Ratha Sor; Dr. Sokun Prum (jfpublisher, 2026)
Even the importance of student satisfaction and loyalty for higher institutions has increasingly been acknowledged, there is a lack of academic study on the building of the conceptual model. This study focused to investigate the factors influencing the student satisfaction and loyalty in selected universities in Phnom Penh, Cambodia. The conceptual model was developed by theoretical framework as the stimulus-organism-response (SOR), service quality and along with four theoretical frameworks. The study highlighted the determinants of student satisfaction, consisting of teacher quality, college administrative, campus life and social integration, infrastructure facilities and institution reputation, while student satisfaction itself plays as mediator. With synthetization of foregoing empirical papers, the findings exhibited that the proposed factors have a significant influence on student satisfaction. Besides, the student satisfaction significantly mediates between these antecedences and student loyalty. These pave the way for further research employing particular advanced statistical techniques to produce better results.